Kompetensi Multibudaya Konselor Dalam Konseling Kelompok Sebagai Upaya Mengatasi Bias Budaya Pada Anggota Kelompok - Alfi Rahmi; Neviyarni Neviyarni; Netrawati Netrawati (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2022)
Group Counseling is one type of service in Guidance and Counseling. Implementation of group counseling needs to pay attention to the characteristics of group members. There are cultural differences that underlie each member of the group. The purpose of this study is to formulate the importance of the multicultural competence of counselors in addressing cultural biases that exist in group counseling activities. To reveal the data of this study, a literature review methodology was used with reference sources in the form of articles, books, and information from technology and communication media that were following the topics discussed. The results of the discussion revealed that these differences in cultural characteristics need to be addressed properly by group leaders with the right knowledge, attitudes, and skills. To build good group dynamics in a multicultural counseling atmosphere, group leaders should have competence. Multicultural competencies that must be mastered by counselors are counselor awareness of cultural values ​​and biases from within themselves, counselor awareness about counselee views, and culturally appropriate intervention strategies. Mastery of this multicultural competence must be bound by values ​​and ethics. There is a code of ethics that oversees the implementation of group counseling service activities. Problem-solving group members in group counseling need to use the right approach. The group leader must be able to choose an approach according to the characteristics of the problems faced by group members.